Activity of topotecan as topoisomerase IB inhibitor - Bali, Semiha Kevser. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
Human Topoisomerase I (TopoI) is an enzyme that relaxes the supercoils on the DNA. First, it creates a nick only on one strand of DNA by covalently binding to it, and relaxes DNA by rotating the nicked strand around the intact one and re-ligating it back. Camptothecin (CPT) and its derivatives are known to target only Topoiso merase enzymes. When CPT or its analog Topotecan (TPT) is added to DNA-TopoI complex, the drug intercalates where the nick occurs and prevents relaxation by turn ing TopoI into a DNA-damaging agent. TPT has two forms: lactone and carboxylate forms, which are in equilibrium at neutral pH. It was shown that the lactone form is the “active” form of the drug, however, in the crystal structure of ternary complex (TPT DNA-TopoI) both forms were intercalating at the same site. This ﬁnding raises the question regarding the cause of activity diﬀerence between two forms despite binding to the same site. In this study, using Molecular Dynamics (MD) and hybrid Quantum Mechanics/Molecular Mechanics (QM/MM) approaches the diﬀerence in activity is in vestigated. 450 ns long MD simulation of both forms was performed and interaction energies were calculated using QM/MM method. Decomposition of the interaction energies showed that the interaction with TopoI is the reason for their activity diﬀer ence. When the contribution of residues on the interaction energy was investigated, it was found that the most striking eﬀect was due to K532 residue, and the topological analysis has further supported this ﬁnding. In addition, when the hydrogen bond net works around the drug were investigated, it was observed that in lactone form K532 was interacting with the drug, which was lost in carboxylate form. In conclusion, lac tone form of TPT is held by K532 residue strongly and N722 forms a hydrogen bond network around the binding pocket in the lactone form only.
Keywords: DNA topoisomerases.